Pengaruh Sodium Benzoat Terhadap Ketahanan Warna Pewarna Alami Dari Kulit Alpukat Terhadap Cahaya Dan Pencucian - Nisrina Zahrah, Firyal; Rizkia, Vika; Djonaedi, Emmidia (Fakultas Teknik UMSU, 2025)
Synthetic dyes in the textile industry are toxic and pollute the environment. As an alternative, natural dyes from avocado skin (Persea americana) have the potential to be used because they contain phenolic compounds such as flavonoids and tannins. However, its color stability is still a challenge. This study aims to evaluate the color stability of avocado skin pigments on cotton fabrics, with and without the addition of sodium benzoate as a stabilizer. The pigments were extracted through maceration using 96% ethanol, then applied to cotton fabrics and tested against light exposure and washing. Analysis was carried out on the parameters ΔE, Optical Density, and CMYK. The results showed that samples with sodium benzoate were more stable in color (ΔE = 1.34) than without stabilizer (ΔE = 3.31). Sodium benzoate is effective in maintaining the intensity and spectral stability of pigments, supporting their use in environmentally friendly natural textile dyes.